2007
DOI: 10.1021/tx700026r
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Depleted Uranium Is Cytotoxic and Clastogenic to Human Lung Cells

Abstract: Depleted uranium (DU) is commonly used in military armor and munitions, and thus, exposure of soldiers and non-combatants is potentially frequent and widespread. DU is considered a suspected human carcinogen, affecting the bronchial cells of the lung. However, few investigations have studied DU in human bronchial cells. Accordingly, we determined the cytotoxicity and clastogenicity of both particulate (water-insoluble) and soluble DU in human bronchial fibroblasts (WTHBF-6 cells). We used uranium trioxide (UO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Particulate depleted uranium (DU), widely suspected as one of the prime causes of PGWS associated pathologies, compounds were demonstrated to induce time and concentration-dependent cytotoxic (producing a toxic effect on cells) and clastogenic (causing disruption or breakages of chromosomes) effects in human lung cells. The types of aberrations seen with treatment of particulate DU are consistent with those induced by other carcinogenic metals (Wise et al, 2007). Tests of 5 Gulf War Veterans in 2007 analysed by Wayne State University Medical staff revealed the 5 Veterans studied have severe chromosome damage.…”
Section: A Diseasome Overlap With Persian Gulf War Syndrome?supporting
confidence: 52%
“…Particulate depleted uranium (DU), widely suspected as one of the prime causes of PGWS associated pathologies, compounds were demonstrated to induce time and concentration-dependent cytotoxic (producing a toxic effect on cells) and clastogenic (causing disruption or breakages of chromosomes) effects in human lung cells. The types of aberrations seen with treatment of particulate DU are consistent with those induced by other carcinogenic metals (Wise et al, 2007). Tests of 5 Gulf War Veterans in 2007 analysed by Wayne State University Medical staff revealed the 5 Veterans studied have severe chromosome damage.…”
Section: A Diseasome Overlap With Persian Gulf War Syndrome?supporting
confidence: 52%
“…An analysis of Gulf War I veterans exposed to alpha particle emitting depleted uranium has also identified a significant 50% increase in HPRT mutant frequency compared to a low exposure group [106] and a number of other studies have also observed the mutagenic and clastogenic potential of depleted uranium exposure [107,108]. …”
Section: Genetic Effectsmentioning
confidence: 99%
“…[3, 4]. The high density (19.1 g/cm 3 ) and pyrophoric properties of depleted uranium make it desirable as fuel for nuclear reactors and as raw material for making both ammunition and tank armor for the military [5, 6]. …”
Section: Introductionmentioning
confidence: 99%